Exploring noninvasive matrices for assessing long-term exposure to phthalates: a scoping review - Chen, Li-wen; Chen, Xin; Mo, Hua-yan; Shan, Chun-han; Zhu, Ruo-ping; Gao, Hui; Tao, Fang-biao (Frontiers in Public Health, 2024)
The phthalic acid esters (PAEs) are one class of the most abundant and frequently studied pseudo-persistent organic pollutants. Noninvasive urine is an effective substrate for evaluating PAE exposure, but repeated sampling is needed to overcome this bias. This adds much work to on-site collection and the cost of detection increases exponentially. Therefore, the aim of this study was to conduct a scope review to describe the detection methods and validity of the use of other noninvasive matrices, such as nails and hair, for assessing long-term exposure to PAEs. The PubMed, Web of Science and China National Knowledge Infrastructure (CNKI), electronic databases were searched from 1 January 2000 to 3 April 2024, and 12 studies were included. Nine and three studies used hair and nails, respectively, as noninvasive matrices for detecting PAE exposure. Five articles compared the results of nail or hair and urine tests for validity of the assessment of PAE exposure. The preprocessing and detection methods for these noninvasive samples are also described. The results of this review suggest that, compared with nails, hair may be more suitable as a noninvasive alternative matrix for assessing long-term exposure to PAEs. However, sample handling procedures such as the extraction and purification of compounds from hair are not uniform in various studies; therefore, further exploration and optimization of this process, and additional research evidence to evaluate its effectiveness, are needed to provide a scientific basis for the promotion and application of hair detection methods for assessing long-term PAE exposure levels.